2018
DOI: 10.1371/journal.pone.0204259
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of intestinal parasites versus knowledge, attitude and practices (KAPs) with special emphasis to Schistosoma mansoni among individuals who have river water contact in Addiremets town, Western Tigray, Ethiopia

Abstract: BackgroundIntestinal parasite infections are major public health problems in resource-limited countries that adversely affect the well-being of millions. Among these, intestinal schistosomiasis is a serious public health problem in tropical and sub-tropical countries.MethodsA Community based cross sectional study was conducted from February to April 2017 in Addiremets town, Ethiopia. Socio-demographic associated risk factors and knowledge, attitude and practices of individuals regarding intestinal parasite inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

16
21
17

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(54 citation statements)
references
References 18 publications
16
21
17
Order By: Relevance
“…This poor maternal knowledge, negative attitude, and poor maternal practice. In this study, the total level of mothers' knowledge was lower than a study that was done in Tigray, Ethiopia in which 94.4% of respondents had good knowledge about intestinal parasitoids prevention (48). This discrepancy might be because of the different study populations.…”
Section: Discussioncontrasting
confidence: 74%
“…This poor maternal knowledge, negative attitude, and poor maternal practice. In this study, the total level of mothers' knowledge was lower than a study that was done in Tigray, Ethiopia in which 94.4% of respondents had good knowledge about intestinal parasitoids prevention (48). This discrepancy might be because of the different study populations.…”
Section: Discussioncontrasting
confidence: 74%
“…This may contribute for poor hygienic practice, and low level of and 48.9% (43.9, 54.0) of respondents were had poor maternal knowledge, negative attitude, and poor maternal practice. In this study, the total level of mothers' knowledge was lower than a study that was done in Tigray, Ethiopia in which 94.4% of respondents had good knowledge about intestinal parasitoids prevention (48). This discrepancy might be because of different study population.…”
Section: Discussioncontrasting
confidence: 72%
“…In this study 78.0% of mothers wash their children's hand before meal. This finding is lower than a study from Tigray that reported 301(100) respondents wash their hands before meal (48). The disagreement might be due to geographic difference, and availability of water.…”
Section: Discussioncontrasting
confidence: 71%
See 2 more Smart Citations